Language shapes Ecumenical Theology: An example of Slovak Language - Batka, L'ubomír (Studi e materiali di storia delle religioni, 2020)
The article offers information on ecumenical theology. It mentions that ecumenism is a linguistic endeavor in finding a common expression of communion in the meaning of used modus loquendi. It also mentions about the importance of common language for the transformation of human heart and mind by the Word of God.